MAKING WEB FULL PASKIBRA INDONESIA KEC.KEBAYORAN LAMA USING MACROMEDIA FLASH MX 2004 - Suparman Suparman; Soenarto Usna, SSi, MMSI Soenarto Usna, SSi, MMSI (Jurnal Sistem Informasi, 2006)
Full paskibra Indonesia is a youth organization located in the guidance of the Officeof Sports and Youth and was instrumental helping the school to avoid theincreasingly rampant student fights for life instill nationalism, patriotism and unity atthis time.With existence of information technology such as Internet writer intends to make amedia tool to deliver news, activities and other information related to the currentpaskibra to its members in particular and to the community at large.